The Factors Influencing Repurchase Intention of Craft Beer Tuatara - Siti Rahmawati Yuswanda; Jony Oktavian Haryanto; Donald Samuel Slamet Santosa (FIRM Journal of Management Studies, 2022)
The existence of craft beer in Indonesia has not been widely known. However, the intention of consuming craft beer is relatively high as the sales of PT. Beervana has been increasing. The main objective of this research is to find out how the factors influence repurchase intention of craft beer. This study uses quantitative method to analyze the data that have been collected from 200 respondents through a questionnaire using multiple linear regression. The findings of this study indicate that product characteristics, perceived quality, country of origin, and conformity significantly influence consumer repurchase intention. However, packaging is found to not have significant influence towards consumer repurchase intention.